1998
DOI: 10.1161/01.atv.18.5.816
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Rabbits With Either Hirudin, Ancrod, or Warfarin Significantly Reduces the Immediate Uptake of Fibrinogen and Platelets by the Deendothelialized Aorta Wall After Balloon-Catheter Injury In Vivo

Abstract: Abstract-Fibrinogen and platelets rapidly saturate the exposed subendothelium of a freshly deendothelialized aorta in vivo. As thrombin generated within the site of injury is largely responsible for fibrin(ogen) deposition, we questioned whether various anticoagulant treatments would inhibit uptake of both fibrinogen and platelets in vivo. Rabbits were anticoagulated by pretreatment with either Warfarin, Ancrod, or recombinant hirudin. Each anesthetized, anticoagulated (or saline-injected control) rabbit was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…38 The dose of ancrod was based on our experience with rabbits and a previous study with mice. 37,39 Mice received ancrod (Sigma Chemical) in 4 bolus injections (1 unit in 0.2 mL of saline each) via the retro-orbital sinus, starting 16 hours before LPS challenge (−16 hours, −8 hours, 0 hours, and +8 hours).…”
Section: Ancrod Treatmentmentioning
confidence: 99%
“…38 The dose of ancrod was based on our experience with rabbits and a previous study with mice. 37,39 Mice received ancrod (Sigma Chemical) in 4 bolus injections (1 unit in 0.2 mL of saline each) via the retro-orbital sinus, starting 16 hours before LPS challenge (−16 hours, −8 hours, 0 hours, and +8 hours).…”
Section: Ancrod Treatmentmentioning
confidence: 99%
“…To determine the contribution of fibrin deposition to myocardial I/R injury, rabbits (n ϭ 5) were treated with ancrod, a defibrinogenating agent. 26 Ancrod cleaves only the A-chains of fibrinogen producing soluble, uncrosslinked fibrin-fibrinogen degradation products that are cleared by the reticuloendothelial system. Ancrod (Sigma Chemical Co., St. Louis, MO) was administered as previously reported.…”
Section: In Situ Coronary Ligation Modelmentioning
confidence: 99%
“…Ancrod (Sigma Chemical Co., St. Louis, MO) was administered as previously reported. 26 Rabbits received ancrod intravenously beginning with a bolus dose of 1.0 IU/kg, followed by a second bolus dose (1.0 IU/kg) 1 hour later, and a third bolus dose (2.0 IU/kg) 3 hours later. The I/R protocol was initiated 6 hours after the first ancrod dose.…”
Section: In Situ Coronary Ligation Modelmentioning
confidence: 99%
“…On the other hand, we determined the N-terminal sequence of rabbit fibrinogen in this study. In the rabbit sequence of the N-terminal region corresponding to FPA (A· 1-16) or fibrinopeptide B (FPB; Bß 1-13), only a few amino acid residues (e.g., Phe 8 and Arg 16 in FPA, Arg 13 in FPB) were homologous between rabbit and human or bovine sequences. The variability of FPA and FPB sequences among mammalian species had been reported by Blombäck et al [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Hatton et al [8] demonstrated that thrombin converted fibrinogen to fibrin, and that fibrin-bound thrombin was deposited on the exposed subendothelium after balloon-catheter injury. Speidel et al.…”
Section: Introductionmentioning
confidence: 99%